2014
DOI: 10.1177/2167702614545479
|View full text |Cite
|
Sign up to set email alerts
|

Stress and the Development of Cognitive Vulnerabilities to Depression Explain Sex Differences in Depressive Symptoms During Adolescence

Abstract: Although cognitive vulnerabilities to depression have received considerable empirical support, little research has evaluated the differential development of cognitive vulnerabilities in adolescent girls and boys. The current study examined the role of stressful life events, as well as sex differences in reactivity and exposure to stress, in the development of negative cognitive style and rumination in a multi-wave study of 382 adolescents. Path analyses indicated that interpersonal dependent stress predicted h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 60 publications
(80 reference statements)
5
75
0
Order By: Relevance
“…In addition to increased rates of SI among adolescent girls, research has consistently demonstrated that adolescent girls also have greater negative inferential styles (Hankin and Abramson 2002) and are more likely to develop ruminative tendencies during the adolescent years (e.g., Hamilton et al 2015). Although few studies have evaluated sex as a potential moderator of the relationship between cognitive factors and SI, numerous studies have demonstrated that cognitive vulnerabilities predict depression more strongly among adolescent girls than boys (e.g., Jose and Brown 2008; Mezulis et al 2010).…”
Section: Sex Differences In the Pathway Between Cognitive Factors Andmentioning
confidence: 99%
“…In addition to increased rates of SI among adolescent girls, research has consistently demonstrated that adolescent girls also have greater negative inferential styles (Hankin and Abramson 2002) and are more likely to develop ruminative tendencies during the adolescent years (e.g., Hamilton et al 2015). Although few studies have evaluated sex as a potential moderator of the relationship between cognitive factors and SI, numerous studies have demonstrated that cognitive vulnerabilities predict depression more strongly among adolescent girls than boys (e.g., Jose and Brown 2008; Mezulis et al 2010).…”
Section: Sex Differences In the Pathway Between Cognitive Factors Andmentioning
confidence: 99%
“…In particular, youth at risk for depression, such as children of depressed mothers, do not demonstrate developmental increases in RSA (Field & Diego, 2008; Gentzler et al, 2012), suggesting that high-risk youth may be at greater risk for atypical reactivity. Further, there are a number of changes that occur during adolescence that may influence the development of atypical HRV reactivity, including pubertal and biological influences (Casey, Jones, & Hare, 2008; Susman & Rogol, 2004), and greater exposure and reactivity to stress (Hamilton, Stange, Abramson, & Alloy, 2015; Romeo, 2013). Thus, adolescence may be a period in which individuals with atypical HRV reactivity are at increased risk for depression, thereby further highlighting the need for a thorough review of HRV reactivity and depression among both youth and adults.…”
Section: Introductionmentioning
confidence: 99%
“…We also evaluated sex differences in the relationship between attentional shifting and rumination and depression onset. This was important given that research has found that girls develop a more ruminative response style and higher rates of depression than boys by mid-adolescence 1,24 . However, the literature has provided mixed evidence about the presence of sex differences in the relationship between rumination and depression during adolescence 25 , and no studies to our knowledge have evaluated sex differences in the relationship between attentional shifting and first onset of major depression.…”
mentioning
confidence: 99%